Devonian core complex exhumation and Cenozoic decollements as alternatives to the Ellesmerian Orogeny - Koehl, Jean-Baptiste P. (2018)
Poster presentation at ARCEx Annual Conference 2018, Longyearbyen, Svalbard, 09.10. - 11.10.18. https://arcex.no/arcex-2018/. The Ellesmerian Orogeny (Piepjohn et al., 2000) is a short-lived contractional–transpressional event that occurred in the Late Devonian–Mississippian, i.e., after Devonian collapse of the Caledonides and prior to Carboniferous rifting. Thus far, this episode of contraction–transpression was required to explain the presence of undeformed Carboniferous–Permian sedimentary rocks on top of folded Upper Devonian strata in central Spitsbergen. The orogen is poorly constrained in other parts of the Arctic due to the lack/poor exposure of Devonian–Carboniferous sedimentary rocks (Rippington et al., 2010). We present an alternative model involving core complex exhumation through continuous, decreasing, Devonian–Carboniferous extension during the collapse of the Caledonides, and (partial) strain decoupling during Cenozoic transpression in Svalbard.